Implementasi Keperawatan dengan Pengendalian Diri Klien Halusinasi pada Pasien Skizofrenia - Juli Andri; Henni Febriawati; Panzilion Panzilion; Selvia Novita Sari; Diko Anandika Utama (Jurnal Kesmas Asclepius, 2019)
The purpose of this study was to determine the effect of implementing nursing with hallucinatory client self-control in schizophrenic patients at Soeprapto Mental Hospital in Bengkulu Province. The research design used was quasi experiment with one group pre-test and post-test design approaches. The results of this study obtained a value of p = 0.001 <α 0.05, which means there is an influence of nursing supplementation with hallucinatory client self-control in schizophrenic patients at the Soeprapto Mental Hospital in Bengkulu Province. Conclusion, there is the effect of nursing supplementation with hallucinatory client self-control in schizophrenic patients at Soeprapto Mental Hospital in Bengkulu Province. Keywords: Hallucinations, Implementation of Nursing, Self-Control.